1998
DOI: 10.1046/j.1365-3156.1998.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni, intestinal parasites and perceived morbidity indicators in schoolchildren in a rural endemic area of western Côte d'Ivoire

Abstract: SummaryThere is a great need for rapid and low-cost identification of communities at high risk of intestinal schistosomiasis. We report the development of a questionnaire approach that may do so. In the first phase, 209 schoolchildren from 3 neighbouring villages in a rural area endemic for intestinal schistosomiasis in western Côte d'Ivoire were screened for Schistosoma mansoni and other helminths on 4 consecutive days using Kato-Katz thick smears. Daily infection prevalences of S. mansoni were high (60%᎐71%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…A potential confounding effect can be expected in areas with high levels of S. mansoni infections, since infected individuals report diarrhoea more often compared with non-infected individuals (GRYSEELS, 1992). In our own work in the same area we found an odds ratio of 1.7 (95% CI 04-3.6) for this association (UTZINGER et al, 1998). In summary, reported diarrhoea was the only useful symptom for the identification of E. histolytica/E. dispar infections in our population surveyed, while no useful sign or symptom was found for the other intestinal parasites.…”
Section: Discussionmentioning
confidence: 42%
See 3 more Smart Citations
“…A potential confounding effect can be expected in areas with high levels of S. mansoni infections, since infected individuals report diarrhoea more often compared with non-infected individuals (GRYSEELS, 1992). In our own work in the same area we found an odds ratio of 1.7 (95% CI 04-3.6) for this association (UTZINGER et al, 1998). In summary, reported diarrhoea was the only useful symptom for the identification of E. histolytica/E. dispar infections in our population surveyed, while no useful sign or symptom was found for the other intestinal parasites.…”
Section: Discussionmentioning
confidence: 42%
“…The marked relationship between reported blood in stool and intestinal schistosomiasis caused by S. mansoni is described elsewhere (UTZINGER et al, 1998). In the present paper, emphasis is placed on E. histolytica/E.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…14,18 Other studies focused on individual diagnosis of S. mansoni, and self-reported blood in stool was found to give the best diagnostic performance, but sensitivity and specificity values were only moderate. [19][20][21][22] Another approach of risk assessment was used in Brazil, where sociodemographic variables and recalled water-contact patterns were investigated in addition to perceived symptoms as predictors for an infection with S. mansoni. Results showed that questionnaires might be an alternative for self-diagnosis of S. mansoni.…”
Section: Introductionmentioning
confidence: 99%